As cidades pequenas na região metropolitana de Campinas-SP: dinâmica demográfica, papéis urbanos e (re) produção do espaço - Moreira Júnior, Orlando [UNESP] (2014)
This thesis is the result of the development of a survey conducted in cities with less than 50,000 inhabitants, in the metropolitan region of Campinas-SP. It is focused on achieving an analysis that allows understanding how the trajectory of metropolization, productive practices and the capital’s reproduction generate differentiated and hierarchical spaces, marked by different socioeconomic and population processes. Although it comprehends an analysis from the entire metropolis, the main focus was to understand the interactions and the characteristics of small towns in the region, aimed at grasping the practices and relationships established intra and intercity in these realities. The results allowed the comparability with other researches undertaken on the subject. This research enabled us to identify on one hand, aspects that resemble the dynamics of small towns in a metropolitan region of those located in non-metropolitan areas. On the other hand, it allowed pointing particular characteristics undertaken by small towns at the process of metropolization. In this sense, it is expected that the research may contribute, from a qualitative point of view, the study of small towns and that may indicate new possibilities to think theoretically and methodologically building a common agenda among researchers of the subject